1999
DOI: 10.1029/1999gl002320
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the South Java Current in the Indo‐Australian Basin

Abstract: Abstract.A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 9 publications
(2 reference statements)
9
106
0
2
Order By: Relevance
“…The poleward propagation of the downwelling coastal Kelvin wave raises the sea level along the Indonesian wave guide of Sumatra and the Lesser Sunda Islands Liu, 1993, 1994], causes maximum eastward flow of the semi-annually reversing South Java Current [Quadfasel and Cresswell, 1992], and may temporarily reverse the alongstrait pressure gradient within the Lesser Sunda passages [Hautala et al, 2001]. In May 1997, a semiannually forced Kelvin wave resulted in eastward flow of very fresh, warm water in the South Java Current [Sprintall et al, 1999], with subsequent northward flow observed up through Lombok Strait and past a mooring in Makassar Strait ].…”
Section: Model Skillmentioning
confidence: 99%
“…The poleward propagation of the downwelling coastal Kelvin wave raises the sea level along the Indonesian wave guide of Sumatra and the Lesser Sunda Islands Liu, 1993, 1994], causes maximum eastward flow of the semi-annually reversing South Java Current [Quadfasel and Cresswell, 1992], and may temporarily reverse the alongstrait pressure gradient within the Lesser Sunda passages [Hautala et al, 2001]. In May 1997, a semiannually forced Kelvin wave resulted in eastward flow of very fresh, warm water in the South Java Current [Sprintall et al, 1999], with subsequent northward flow observed up through Lombok Strait and past a mooring in Makassar Strait ].…”
Section: Model Skillmentioning
confidence: 99%
“…The WOCE observation tracks did not cover Java-Sumatra coast well, especially the south Java shelf region. A strong semiannual South Java Current (SJC) was observed from one year mooring record [18]. Recently Sprintall et al [8] updated the SJC and South Java Under Current (SJUC) as they were inferred from the current moorings situated at Ombai Strait.…”
Section: Introductionmentioning
confidence: 99%
“…The observations made from current meters moored at the Java coast suggest that the arrival of Kelvin wave originating from the equatorial Indian Ocean causes a warming of water column in the south Java coast. Following the wave passage, the coastal currents along south Java are north-westward and the prevailing southeasterly monsoon winds lead to upwelling of salty subsurface water [18].…”
Section: Introductionmentioning
confidence: 99%
“…During winter monsoon, the South Java Current (SJC) flows southeastward and this flow becomes strong in May and November when westerly wind bursts formed during the monsoon transition (Quadfasel and Cresswell, 1992;Sprintall et al, 1999). On the other hand, the SJC flows as a westward current along the coast of Java during the summer monsoon (May-October).…”
Section: Regional Settingmentioning
confidence: 99%